2021
DOI: 10.1111/pbi.13758
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing and transcriptome analyses provide insights into the origin and domestication of water caltrop (Trapa spp., Lythraceae)

Abstract: Humans have domesticated diverse species from across the plant kingdom; however, our current understanding of plant domestication is largely founded on major cereal crops. Here, we examine the evolutionary processes and genetic basis underlying the domestication of water caltrop (Trapa spp., Lythraceae), a traditional, yet presently underutilized non-cereal crop that sustained early Chinese agriculturalists. We generated a chromosome-level genome assembly of tetraploid T. natans, and then divided the allotetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 101 publications
1
27
0
1
Order By: Relevance
“…Within rosids, the main conflicts with previous phylogenetic analyses related to the position of Myrtales and the phylogenetic relationships within clade II. Our results indicated that Myrtales are sister to other rosids, which is consistent with most analyses [37,[45][46][47][48][49][50][51][52][53]56] but not with an analysis of 1000 transcriptomes that suggests that Myrtales are nested within other malvids [27]. Within rosid clade II, our results support the hypothesis that Fagales are sister to the other species and Cucurbitales are sister to Fabales, whereas previous studies have concluded that Fagales and Fabales cluster together and Cucurbitales and Rosales are sister clades [27,43,50].…”
Section: Phylogenetic Relationship Between Buxales and Other Eudicot ...supporting
confidence: 90%
“…Within rosids, the main conflicts with previous phylogenetic analyses related to the position of Myrtales and the phylogenetic relationships within clade II. Our results indicated that Myrtales are sister to other rosids, which is consistent with most analyses [37,[45][46][47][48][49][50][51][52][53]56] but not with an analysis of 1000 transcriptomes that suggests that Myrtales are nested within other malvids [27]. Within rosid clade II, our results support the hypothesis that Fagales are sister to the other species and Cucurbitales are sister to Fabales, whereas previous studies have concluded that Fagales and Fabales cluster together and Cucurbitales and Rosales are sister clades [27,43,50].…”
Section: Phylogenetic Relationship Between Buxales and Other Eudicot ...supporting
confidence: 90%
“…In addition, WUSCHEL-related homeobox (WOX) genes are also involved in leaf development and they regulates the expression of CIN class TCPs (Jha et al, 2020; Wang et al, 2020). Many aquatic species have evolved to be polyploid during species differentiation (Albert and Renner, 2020; Lu et al, 2021; Prancl et al, 2014), and polyploid was verified to be one of the strategies for plants to expand their ranges and invade new environments by endowing polyploid progenies with novel traits (Cheng et al, 2021a). In addition, gene expansion (especially TFs) is important for plant evolution (Feller et al, 2011; Mathew and Agarwal, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Amphibious plants are those that can grow in both terrestrial and submerged conditions and evolved unique advantages between different environments (Agarie et al, 1997). Profound investigations have been performed on terrestrial plants, and a few genomic data of aquatic plants were also recently reported (Lu et al, 2021; Shi et al, 2022). However, genomic data of amphibious plants are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…We wished to include as many orders as possible in our study, ideally with access to at least six genomes with high quality, preferably chromosome-level, assemblies, distributed among at least three different families. At the time of data collection, we could obtain suitable data from three fabid orders, Fagales [2027], Cucurbitales [2833], Malpighiales [3439]; three malvid orders, Myrtales [4044], Malvales [4550] and Sapindales [5161]; one campanulid order, Asterales [6268]; and three lamiid orders, Gentianales [69–75], Lamiales [76–82] and Solanales [8388], plus Ericales [8994]. Other orders with sufficient genomes available were not selected, such as Fabales, because representative genomes from only one or two families were available, or Brassicales, which is the subject of a concurrent publication.…”
Section: Resultsmentioning
confidence: 99%